An Empirical Study on the Adoption Intention of IoT-based Medical Information Services: Focusing on the Moderating Effect of User Usability - Oh, Jai-woo (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: Based on the anticipation that IoT-based smart healthcare systems will lead to improvement of the quality and efficiency of healthcare services, an empirical analysis was conducted, with the aim of proposing the necessary strategic measures to enhance the adoption intention among potential users.Methods/Statistical analysis: A survey was carried out from February to March 2019 using the convenient sampling method, targeting the members of a user group interested in the advancement of smart healthcare. A total of 327 questionnaire forms were returned, of which 321 forms, excluding the 6 forms that were deemed unsuitable, were used in analyses of descriptive statistics, Pearson correlation coefficient analysis and multiple regression analysis, using SPSS 22.0.Findings: First, a multiple regression analysis was carried out in order to examine the effects of the Selective Attributes of an IoT-based smart healthcare system on the intention to accept the system. The results showed a positive (+) correlation between the motivation for use and service suitability among the Selective Attributes and the adoption intention, while the correlation between the adoption intention and user innovativeness was not statistically significant. Second, the user usefulness was found to have a moderating effect between the adoption intention and the Selective Attributes such as user innovation, motivation for use, and service suitability. The analysis results showed that the interaction effect of usefulness was statistically significant, meaning that as the user usefulness increased, the adoption intention also increased.Improvements/Applications: This study analyzed the causality of Selective Attributes in the introduction of IoT- based smart healthcare system and analyzed the interaction effect of user usability.